THE EFFECT OF IFRS ADOPTION ON REAL EARNINGS MANAGEMENT WITH THE MODERATING ROLE OF BOARD CHARACTERISTICS - Nanang, Sheila Elita; Imelda, Elsa (Graduate Program of Universitas Tarumanagara, 2025)
This study was carried out with the objective of determining the effect of International Financial Reporting Standards (IFRS) on Real Earnings Management (REM) practices using board characteristics as a moderating variable that determined by board size, board independence, CEO duality, board expertise, and gender diversity. This research employs a quantitive approach, utilizing purposive sampling technique with a sample of 31 non-cylical consumer sector companies that listed on Indonesia Stock Exchange (IDX) for the periods of 2009-2011 and 2019-2023. Data is processed using STATA application with the PCSE Estimator feature in testing the hypothesis. This research results indicate that IFRS, board independence, board expertise, and gender diversity do not exert a substantial on REM. While board size exerts a considerable negative influence on REM and CEO duality exerts a considerable positive influence on REM. In addition, it was found that board size moderates significantly positive for the correlation between IFRS and REM, where CEO duality and board expertise moderate significantly negative. However, there’s no moderating effect of board independence and gender diversity variables were found in this study. So it can be concluded that board characteristics partially moderate the correlaction between IFRS and REM.